O quilombo Forte Príncipe da Beira e os desfios socioambientais frente aos conflitos territoriais de uso e ocupação da terra - Shuassb, Márcio Josué Nunes (2024)
This dissertation examines the context experienced by the quilombolas of Forte Príncipe da Beira, in the municipality of Costa Marques, state of Rondônia, with the general objective of evaluating the relationship of coexistence between the quilombola community and the Army in the Real Forte Príncipe da Beira, considering the need for the affirmation of quilombola identity through territoriality in this region, where conflicts between the two parties involved were intensified with the officialization of the certificate of self-recognition of the community of Forte Príncipe da Beira as a remnant of a quilombo community issued by the Palmares Cultural Foundation. The history of the occupation of the Amazon region, especially in the area of Forte Príncipe da Beira, has undergone several social and territorial changes over the centuries. Initially explored by the Portuguese, with the labor of indigenous and enslaved Afro-Brazilians, the region was militarized for fortification, resulting in the construction of the Nossa Senhora da Conceição Fortress and Forte Príncipe da Beira, in the 18th century. After the military decline, the area was abandoned, but descendants of the builders continued to inhabit Vila de Conceição. In the 1960s, the military dictatorship encouraged the exploitation of mineral resources, timber, and land for colonization, generating conflicts with indigenous and traditional communities. Pressure on the quilombola territory of Forte Príncipe da Beira increased, resulting in forced migration and urban integration. Conflicts arose from issues such as land grabbing, forestry, agriculture, mining, and urban expansion. The issuance of the quilombola self-recognition certificate in 2005 exacerbated conflicts between the military and quilombolas. Quilombola resistance, with a territorial identity based on ethnicity and local practices, is fundamental to the community, which seeks freedom and meaning. Quilombolas, formed by descendants of enslaved Africans and excluded indigenous people, resisted and built a territorial identity after abolition. Furthermore, we highlight the territorial rights of quilombolas since the 1988 Constitution, the conflicts with the army, and the historical-cultural and socio-environmental importance of the quilombola communities of the Guaporé Valley.